Pengaruh Pembayaran Cash On Delivery, Program Gratis Ongkir Dan Harga Produk Terhadap Keputusan Pembelian Di Tiktok Shop (Studi Kasus Pada Konsumen Tik Tok Shop Di Desa Druju) - Azizah, Sovia Nur; Khalikussabir, Khalikussabir; Wahyuningtyas, Nanik (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The purpose of this study is to examine how Cash on Delivery (COD), Free Shipping Program, and Product Price influence Purchase Decisions in the TikTok Shop. Using purposive sampling, a sample of 75 respondents was selected. The data was collected through a questionnaire. Multiple linear regression was the data analysis technique employed in this research. The findings indicated that, when analyzed together, both Cash on Delivery and the Free Shipping Program had a significant positive impact, while Product Price also showed a significant positive effect. On the other hand, when analyzed individually, Cash on Delivery and the Free Shipping Program both had a significant positive effect, while Product Price had a positive effect that was not statistically significant on Purchase Decisions. Keywords: Cash On Delivery, Free Shipping Program, Product Price, Purchase Decision